A Geochemical Review of Jabal Al Arab/Southern Syria “Carbonatite” classification (Latakia University Journal -Basic Sciences Series, 2021)
This study provides new indications about Jabal Al Arab/Southern Syria carbonatite, and justifies the exclusion of their carbonates from the international classification upon previous studies. The results were discussed and the conclusions were presented within a geochemical scenario in order to understand the mechanism of formation of these carbonates including their compositions in comparison with similar cases in other volcanic regions around the world. The results show that Jabal Al Arab volcanic carbonates represent sedimentary-origin carbonates that were assimilated during magmatic processes.